Recent Advances in Cryptography and Network Security 2018
DOI: 10.5772/intechopen.76685
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Machine Learning Techniques for Behavioral-Based Biometric User Authentication

Abstract: Authentication is a way to enable an individual to be uniquely identified usually based on passwords and personal identification number (PIN). The main problems of such authentication techniques are the unwillingness of the users to remember long and challenging combinations of numbers, letters, and symbols that can be lost, forged, stolen, or forgotten. In this paper, we investigate the current advances in the use of behavioral-based biometrics for user authentication. The application of behavioral-based biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The system has a continuous user identification using multimodal biometrics to monitor the examiner to ensure that only a valid student takes the exam; a security layer that uses an eye tracker to watch/record student eye movement; and speech recognition to detect unwanted contact. (Mahadi et al, 2018) discussed several techniques and suggested combining (facial recognition and keystroke dynamics) could be the best classifiers in the online course for behavioral biometric authentication. Similarly, (Ghizlane et al, 2019) also suggested a combination of smart cards (to check student's identity) and face recognition techniques (for continuous monitoring of a student's webcam) to detect any suspicious behavior during the online exam and avoid any kinds of cheating attempts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The system has a continuous user identification using multimodal biometrics to monitor the examiner to ensure that only a valid student takes the exam; a security layer that uses an eye tracker to watch/record student eye movement; and speech recognition to detect unwanted contact. (Mahadi et al, 2018) discussed several techniques and suggested combining (facial recognition and keystroke dynamics) could be the best classifiers in the online course for behavioral biometric authentication. Similarly, (Ghizlane et al, 2019) also suggested a combination of smart cards (to check student's identity) and face recognition techniques (for continuous monitoring of a student's webcam) to detect any suspicious behavior during the online exam and avoid any kinds of cheating attempts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The work [17] reviews ongoing authentication methods based on behavioural biometrics. The objective is to determine the classifier techniques that mostly are used for data analysis during authentication process.…”
Section: Related Work On Security Techniques Based On Behavioural Bimentioning
confidence: 99%
“…Yampolskiy and Govindaraju [6] presented a a comprehensive study on behavioral biometrics. Mahadi et al [15] surveyed behavioralbased biometric user authentication, and determined the set of best classifiers for behavioral-based biometric authentication. Sundararajan and Woodard [16] surveyed different 100 approaches that leveraged deep learning and various biometric modalities to identify users.…”
Section: Related Surveys On Biometric Authenticationmentioning
confidence: 99%
“…This amount is calculated without taking into account the economic problems and psychological oppression that victims of this fraud suffer. From the banking sector and businesses, to access to homes, cars, personal computers and mobile devices, biometric technology offers the highest level of security in Gafurov (2007) [4] Not mobile Gait recognition No No No Revett et al (2008) [5] Not mobile Mouse dynamics No No No Yampolskiy and Govindaraju (2008) [6] Not mobile Behavioral-based No No No Shanmugapriya and Padmavathi (2009) [7] Not mobile Keystroke dynamics No No Yes Karnan et al (2011) [8] Not mobile Keystroke dynamics No No Yes Banerjee and Woodard (2012) [9] Not mobile Keystroke dynamics No No Yes Teh et al (2013) [10] Not mobile Keystroke dynamics No No Yes Bhatt et al (2013) [11] Not mobile Keystroke dynamics No No Yes Meng et al (2015) [12] Mobile device All Yes Yes Partial Teh et al (2016) [13] Mobile device Touch dynamics No No Yes Mahfouz et al (2017) [14] Smartphone behavioral-based No No Yes Mahadi et al (2018) [15] Not mobile behavioral-based No No Yes Sundararajan and Woodard (2018) [16] Not mobile All No No Yes [17] Mobile device Face recognition Yes Yes Yes Our survey Mobile IoT device All Yes Yes Yes ML and DM: Machine learning (ML) and data mining (DM) algorithms terms of privacy and privacy protection and secure access.…”
Section: Introductionmentioning
confidence: 99%